Household Welfare, the Labor Market, and Social Programs in Albania - Rashid, Mansoora; Dorabawila, Vajeera; Adams, Richard (Washington, DC: World Bank, 2013)
The paper provides an overview of household welfare, labor markets, and social programs in Albania, outside of its capital, in 1996. At the time, Albania was in a cross roads, from a period of phenomenal growth, to a series of economic crisis, though still ranking as the poorest country in the Central and Eastern Europe Region. The main findings suggest that the majority of the poor are rural, self-employed in agriculture, a result of Albania's large rural population that is mainly employed in subsistence agriculture. These households also have the highest poverty incidence, followed by out of labor force individuals, and the unemployed. Not surprising, the highest poverty incidence is in the rural north, requiring subsidized wheat, and cash transfers to survive difficult winters. Interestingly, migration is a major coping strategy in Albania: households with no migrants, were poorer than those where a family member was working abroad. The study raises concern about the education system, and safety nets, considering there are high drop out rates in basic, and secondary education among the poor, and, education spending is biased against the poor, except in basic education. Moreover, health outcomes are particularly worse among the poor. The study notes that outside of pensions, Albania's social protection system appears moderately well targeted to the poor, however, high tax rates, and limited wage base, makes a contribution based social protection system questionable.